Dinoprostone Gel versus Intra-cervical Foley’s Catheter for Pre-induction Cervical Ripening: An audit - Chawla, Dolly; Tomar, Akanksha; Renjhen, Prachi; malik, neeru (Indonesian Socety of Obstetrics and Gynecology, 2023)
Background One of the common practices in modern obstetrical care is labour induction when foetal and maternal complications arise. We endeavoured to compare the efficacy and safety of the inexpensive mechanical method of induction Foley’s catheter to the more established pharmacological agent Intracervical Prostaglandin E2 gel Method The present prospective randomised control study was carried out on 200 women with a term singleton pregnancy in cephalic presentation, with an unfavourable cervix and a valid indication for induction of labour. The patients were randomly allocated using the chit method to either Foley’s catheter [group A, n=100] or PGE2 gel [group B, n=100] . Augmentation with oxytocin was done if required and labor was closely monitored till delivery and the perinatal outcome and maternal side effects was recorded Quantitative variables were compared using unpaired t-test/Mann-Whitney Test and qualitative variables were compared using Chi-Square test /Fisher’s exact test. Analysis was done using Statistical Package for Social Sciences (SPSS) version 21.0 RESULTThe caesarean section rate did not show a significant difference between the Foley’s group(18%) and PGE2 group(11%) The incidence of fetal distress, Meconium stained liquor and APGAR score <7 at 5 minutes was significantly with PGE2 as compared to group A. (P<.05) Incidence of hyperstimulation of uterus was reported in 6% women who received PGE2 as compared to none in Foley’s group. The induction delivery interval did not show any significant difference between the two groups. CONCLUSION In women undergoing induction of labour at term in resource constraint set ups like ours, Foley catheter is a good alternative to the more established prostaglandin E2 gel, with good efficacy and better neonatal and maternal safety profile. Keywords: cervical ripening; dinoprostone; obstetric labor, induced